The role of the P2X₇ receptor in infectious diseases. - Catherine M Miller (Public Library of Science (PLoS), 2011)
ATP is an extracellular signal for the immune system, particularly during an inflammatory response. It is sensed by the P2X₇ receptor, the expression of which is upregulated by pro-inflammatory cytokines. Activation of the P2X₇ receptor opens a cation-specific channel that alters the ionic environment of the cell, activating several pathways, including (i) the inflammasome, leading to production of IL-1β and IL-18; (ii) the stress-activated protein kinase pathway, resulting in apoptosis; (iii) the mitogen-activated protein kinase pathway, leading to generation of reactive oxygen and nitrogen intermediates; and (iv) phospholipase D, stimulating phagosome-lysosome fusion. The P2X₇ receptor can initiate host mechanisms to remove pathogens, most particularly those that parasitise macrophages. At the same time, the P2X₇ receptor may be subverted by pathogens to modulate host responses. Moreover, recent genetic studies have demonstrated significant associations between susceptibility or resistance to parasites and bacteria, and loss-of-function or gain-of-function polymorphisms in the P2X₇ receptor, underscoring its importance in infectious disease.